2000
DOI: 10.1590/s1516-35982000000400012
|View full text |Cite
|
Sign up to set email alerts
|

Desempenho produtivo em caprinos mestiços no semi-árido do Nordeste do Brasil

Abstract: RESUMO -O estudo foi realizado para avaliar as características produtivas dos caprinos mestiços submetidos às condições climáticas do semi-árido nordestino. Foram utilizadas 657 cabras, as quais foram mantidas em pasto nativo, no período seco, e alimentadas com milho e farelo de soja, e 945 crias mestiças, que foram aleitadas com leite de vaca até 24 horas de vida. As médias das cabras para prolificidade e peso ao parto foram respectivamente 1,69+0,03 e 36,38+0,03 kg, para ½ Pardo Alpina (PA) + ½ Moxotó (MO); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
8

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 0 publications
0
4
0
8
Order By: Relevance
“…Review signals the genetic gain in selection of animals, the annual population growth in terms of herd productivity, and the herd fertility level through the number of hatched products by deliveries every breeding season (SILVA; ARAÚJO, 2000;SARMENTO et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Review signals the genetic gain in selection of animals, the annual population growth in terms of herd productivity, and the herd fertility level through the number of hatched products by deliveries every breeding season (SILVA; ARAÚJO, 2000;SARMENTO et al, 2010).…”
Section: Resultsmentioning
confidence: 99%
“…Alguns autores observaram a influência do sexo sobre os pesos de caprinos em diferentes idades, indicando geralmente superioridade dos machos em relação às fêmeas (Silva & Araújo, 2000, Medeiros et al, 2004, em caprinos de vários grupos raciais. A superioridade dos pesos dos machos pode ser devido ao efeito anabólico dos hormônios sexuais secretados pelos fetos machos que, consequentemente são capazes de absorver mais nutrientes da mãe durante o desenvolvimento pré-natal (Medeiros et al, 2004).…”
Section: Resultsunclassified
“…Some studies showed that race is a risk factor for leptospirosis in small ruminants, in which a greater susceptibility to infection was observed among purebred animals compared with crossbred animals SANTOS et al, 2012). In the semi-arid region of Northeast Brazil, most of the sheep comprise of crossbred races (CEZAR et al, 2004), while the goats belong to native and indeterminate breeds with remarkable robustness (SILVA; ARAÚJO, 2000). Therefore, we suggest the hypothesis that, in addition to environmental conditions, the robustness of the animal species evaluated contributed to the low seropositivity observed in this study.…”
Section: Resultsmentioning
confidence: 99%